2010
DOI: 10.1007/s00240-010-0298-x
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for fabricating artificial kidney stones of different physical properties

Abstract: A simple method for preparing artificial kidney stones with varying physical properties is described. BegoStone was prepared with a powder to water ratio (by weight) ranging from 15:3 to 15:6. The acoustic properties of the phantoms were characterized by using an ultrasound transmission technique, from which the corresponding mechanical properties were calculated based on elastic wave theory. The measured parameters for BegoStone phantoms of different water contents are: longitudinal wave speed (3148 – 4159 m/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 19 publications
1
56
0
1
Order By: Relevance
“…Similarly, stone composition (i.e., flaw distribution) has been identified as influencing the shape and scale parameters of the model in a manner similar to variations in Weibull parameters, though uncovering its precise role within the model requires additional experimentation. The artificial kidney stones used in this study have demonstrated clinical relevance (Esch et al, 2010), but do not necessarily mimic the Weibull parameters of all renal and ureteral stones. Determination of Weibull parameters for kidney stones and correlation with parameters of artificial stones may improve applicability of the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, stone composition (i.e., flaw distribution) has been identified as influencing the shape and scale parameters of the model in a manner similar to variations in Weibull parameters, though uncovering its precise role within the model requires additional experimentation. The artificial kidney stones used in this study have demonstrated clinical relevance (Esch et al, 2010), but do not necessarily mimic the Weibull parameters of all renal and ureteral stones. Determination of Weibull parameters for kidney stones and correlation with parameters of artificial stones may improve applicability of the model.…”
Section: Discussionmentioning
confidence: 99%
“…1(a) shows the ranked failure stresses of various hard and soft (5:1 and 5:2 powder to water mixing ratios, respectively) BegoStone Plus (BEGO USA, Lincoln, RI) phantoms from quasi-static diametral compression [see inset Fig. 1(b)], which has been used to determine the tensile failure strength (r f ) of renal calculi and stone phantoms (Esch et al, 2010;Simmons et al, 2010). Details of the stone preparation and diametral compression test have been described previously (Esch et al, 2010).…”
Section: A Weibull Theory For Brittle Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…Comparable acoustic energies (E + ≈ 40 mJ) were used for each lens during stone comminution experiments (Table 1) because it has been shown that stone comminution efficiency correlates closely with the pulse or accumulated acoustic energy in SWL (51,60,61). BegoStone phantoms used during comminution experiments were fabricated with a 5:1 powder-towater mixing ratio following a previously described protocol to mimic the physical properties of hard kidney stones such as calcium oxalate monohydrate and brushite stones (62). After SWL treatment, fragments were collected, carefully rinsed, air-dried for at least 24 h, sieved sequentially with standardized mesh sizes of 4, 2.8, and 2 mm, and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…8 Stone phantoms were prepared from BegoStone (BEGO USA, Lincoln, RI) at a 15:3 powder-to-water ratio to approximate the properties of calcium oxalate monohydrate. 9 Two 3-mm stone phantoms were placed retrograde into each ureter through a 13/15F, 28-cm access sheath. The 13/15F access sheath was advanced to the level of the mid to distal ureter over one of the Sensor wires under fluoroscopic guidance.…”
Section: Methodsmentioning
confidence: 99%